Microplastic pollution in the marine environment: Sources, impacts, and degradation. - Osamah A. Ahmad; Mamdoh T. Jamal; Hamdah S. Almalki; Abeer H. Alzahrani; Amirah S. Alatawi; Md Fazlul Haque. (Journal of Advanced Veterinary and Animal Research)
Microplastics (MPs) are tiny particles derived from plastic, and their high fragmentation poses a significant threat to the marine environment. MPs can originate from various sources, such as primary or secondary sources as well as internal or external sources. However, in marine environments, MPs mainly enter from external sources, such as plastic waste, debris from land-based activities, tourism, shipping, and atmospheric deposition. MP accumulation in marine ecosystems is also influenced by the use of plastic equipment, aquaculture feed, health products, and particular environmental conditions. Understanding the ecotoxicological effects of environmentally relevant concentrations of MPs on the health of marine organisms is crucial. The effects of MPs on the health of marine organisms are well reported by different studies, highlighting their interactions with a wide range of marine life, including plankton, invertebrates, crustaceans, corals, seagrass, fish, and even humans. Thus, MPs have been reported as a notorious pollutant because of their deleterious impacts on the morphology, physiology, immunology, behavior, reproduction, and heredity of marine organisms. Moreover, most MPs are slowly degradable, and degradation is dependent on various biotic and abiotic factors, resulting in continuous accumulation in the marine environment. This review provides an in-depth explanation of the sources of MPs, along with their impacts on marine organisms, ecosystems, aquaculture, and human health. In addition, it will discuss the degradation of MPs in the marine environment to explore the potential strategies for reducing the harmful impacts of MPs. [J Adv Vet Anim Res 2025; 12(1.000): 260-279]